Gas-Containing Kidney Stones: A Case Report - Putu Herry Juniada; Ni Nyoman Srie Laksminingsih; I Made Dwijaputra Ayusta (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Gas-containing kidney stones are rare cases. The available literature about gas in the kidneys, usually only discusses and distinguishes between two things, namely emphysematous pyelonephritis and emphysematous pyelitis, after getting rid of recent upper urinary tract instrumentation and the presence of fistula with the gastrointestinal tract. To date, there have been only 11 cases of gas-containing kidney stones. We report the 12th case of gas-containing kidney stones (the first from the field of radiology), which is a 69-year-old female with bilateral flank pain, no fever, and no history of other diseases. Physical examination revealed bilateral costovertebral angle tenderness. The plain abdominal radiograph showed a staghorn stone in the right kidney. The non-enhanced CT abdomen showed gas-containing staghorn stones in the right kidney accompanied by hydronephrosis. The patient underwent percutaneous nephrolithotomy. Kidney stone analysis showed oxalate, phosphate, ammonium, calcium, and uric acid components. The etiology and relationship of gas-containing kidney stones with other gas entities in the kidney is still unclear, making it difficult to determine their clinical significance. Radiological examination, especially CT scan, plays a very important role in determining the entity of gas in the kidney.